THE GERMAN ETHNICITY IN THE CULTURAL TOURISM MARKET OF HUNGARY/SOUTH TRANSDANUBIA - Szeidl, Klaudia; Aubert, Antal (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
Due to the changes in the tourism market in the latter years a part of society is not seeking for experiences that can be repeated annually but they favour those tourism attractions which provide real experiences for the visitor. As a consequence of the change of the tourist motivation such a development direction has been started which pays peculiar attention to the discovery and utilisation of local values. The cultural peculiarity of the tourism destinations is greatly depending on the value system of the local dwellers. In this respect South Transdanubia as a tourism region is in a lucky position since on the eastern part of the region we can find the greatest area of the country populated by Germans where the most important values of the Swabian culture subsisted until now. Within the framework of the study the region’s cultural attraction supply elements connected to the German ethnicity will be analysed and evaluated. The investigation is focusing on the analysis of Swabian attractions related to the two groups of heritage tourism, which belongs to the scope of cultural tourism, the intangible cultural heritage and the built cultural heritage. Within the intangible cultural heritage belonging to the category of animated culture the ethnic festivals came into prominence, while within the built cultural heritage belonging to the inanimate culture the research was organised around the country houses.